Structure Fragmentation of a Surface Layer of Commercial Purity Titanium During Ultrasonic Impact Treatment; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Kozelskaya A. I. Anna Ivanovna; Panin A. V. Alexey Viktorovich; Kazachenok M. Marina; Hairullin (Khayrullin) R. R. Rustam Ravilievich; Sinyakova E. Elena; Pochivalov Yu. Yurii; Perevalova O. Olga (2015, 2015)
Title screen